Industrial Production of Proteins with Pichia pastoris—Komagataella phaffii - Giovanni Davide Barone; Anita Emmerstorfer-Augustin; Antonino Biundo; Isabella Pisano; Paola Coccetti; Valeria Mapelli; Andrea Camattari (Biomolecules, 2023)
Since the mid-1960s, methylotrophic yeast Komagataella phaffii (previously described as Pichia pastoris) has received increasing scientific attention. The interest for the industrial production of proteins for different applications (e.g., feed, food additives, detergent, waste treatment processes, and textile) is a well-consolidated scientific topic, and the importance for this approach is rising in the current era of environmental transition in human societies. This review aims to summarize fundamental and specific information in this scientific field. Additionally, an updated description of the relevant products produced with K. phaffii at industrial levels by a variety of companies—describing how the industry has leveraged its key features, from products for the ingredients of meat-free burgers (e.g., IMPOSSIBLE™ FOODS, USA) to diabetes therapeutics (e.g., Biocon, India)—is provided. Furthermore, active patents and the typical workflow for industrial protein production with this strain are reported.